ANALISIS BIBLIOMETRIC PAJAK KARBON DALAM MENDORONG INVESTASI HIJAU DAN KONTRIBUSINYA TERHADAP PEMBANGUNAN INDONESIA - Soewardi, Tiara Juniar (Penerbit Lafadz Jaya, 2025)
The global climate crisis necessitates a transformative approach across various sectors to foster green investment and mitigate carbon emissions, including fiscal policy reforms. This study aims to explore the evolution of academic research on carbon taxes and green investment using a bibliometric analysis. A dataset of 261 documents spanning from 2002 to 2025, sourced from the Scopus database, was analyzed to identify emerging trends, significant keyword clusters, and current research directions. The VOSviewer software, a powerful tool for co-occurrence pattern analysis, was employed to conduct this bibliometric evaluation. The results reveal a substantial increase in academic attention to carbon taxation since 2015, with a shift from macroeconomic policy discussions to microeconomic strategies, green technology, and socio-political considerations. Network, overlay, and density visualizations further highlight the rise of new themes, such as green technology and investment in response to green fiscal instruments. These findings offer valuable policy insights, particularly for developing nations, to design carbon tax policies that not only discourage emissions but also foster green technology innovation. Additionally, the study identifies gaps in research, particularly regarding the interaction between carbon taxes, fossil energy, environmental protection, and low-emission green technology investments.